Clinical and Pathological Characteristics of Autoimmune Hepatitis with Acute Presentation - Yi Shen; Changli Lu; Ruoting Men; Jianping Liu; Tinghong Ye; Li Yang (Canadian Journal of Gastroenterology and Hepatology)
Aim. To study the differences between acute presentation-autoimmune hepatitis (A-AIH) and chronic autoimmune hepatitis (C-AIH). Methods. Through long-term follow-up, 80 patients were included in our study by using the revised international autoimmune hepatitis group (IAIHG) score and were divided into acute and chronic groups for comparison. Results. No significant difference was found in the gender, age, IAIHG score (pretreatment/posttreatment), definite diagnosis rate, extrahepatic autoimmune disease, onset time, or treatment before biopsy between the acute and chronic groups. In terms of clinical symptoms, A-AIH patients were more prone to jaundice, anorexia, yellow urine, and detesting oil than C-AIH patients, but melena only occurred in chronic group (P<0.05). The acute group exhibited more severe injury upon histological evaluation, with lobular inflammation and bile duct injury, especially central necrosis of the lobule, more pronounced in this group (P<0.05). Conclusion. A-AIH had manifestations of acute hepatitis and presented cholestasis. Serum indicators could preliminarily distinguish A-AIH and C-AIH. Histologically, the primary manifestation of A-AIH was lobular inflammation, which was usually accompanied by lobular central necrosis. For the diagnosis of A-AIH, more attention should be paid to long-term follow-up. This study was registered at ClinicalTrials.gov (identifier: NCT02994537).